Social skills: group psychotherapy with chronic schizophrenic patients - Rojas, Roberto (1995)
The study confirms the importance of R.P. Liberman's Group training in social skills for schizophrenic patients and applied in Peru by Sotillo et al. (1991) in a public mental health institution. We applied this same experience in a private psychiatric clinic of Lima. Since the management of patients in public and private institutions are different, we carried out a study to train the staff and to adapt the program. Nine in patients with DSM III-R diagnosis of chronic schizophrenia were selected. The inclusion criteria were: basic behaviors, minimal speech repertoire and no positive symptoms. Twenty-seven behaviors, grouped in 4 areas, were assessed before and after training. Results reveal an increase in the number of social skills in 8 of the 9 sujects that participated in the study.